E-bonds : nowe produkty finansowe kreowane na rynkach elektronicznych - Dziuba, Dariusz T. (E-Bonds : New Financial Products Created on Electronic Markets, 2005)
The Internet has offered possibilities of direct trading in securities. Since the mid 1990s, the use of the Internet has been more and more popular in stock issues, in particular in the US capital market. Alternative markets for trading in securities are created by such instruments as internet e-bonds platforms. It is possible, inter alia, thanks to a rapid progress in IT technologies and regulatory changes. The article presents the idea of electronic-bonds, its possible applications, functions and potential economic benefits
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 158-166